∫ 0 2 π sin 1 1 x cos 9 x d x = B A
The equation above holds true for positive coprime integers A and B . Give your answer as A + B .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That really is brilliant!
I = ∫ 0 2 π sin 1 1 x cos 9 d x = 2 β ( 5 , 6 ) = 1 0 ! 4 ! ⋅ 5 ! = 2 5 2 0 1
⟹ A + B = 1 + 2 5 2 0 = 2 5 2 1
Try using Walli's formula
Let, I So, I = ∫ 0 2 π sin 1 1 x cos 9 x d x = ∫ 0 2 π cos 1 1 x sin 9 x d x = 2 1 ∫ 0 2 π sin 9 x cos 9 x ( sin 2 x + cos 2 x ) d x = 2 1 ∫ 0 2 π sin 9 x cos 9 x d x = 2 1 ∫ 0 2 π sin 9 x cos x ( 1 − sin 2 x ) 4 d x = 2 1 ∫ 0 1 u 9 ( 1 − u 2 ) 4 d u = 2 1 ∫ 0 1 ( u 1 7 − 4 u 1 5 + 6 u 1 3 − 4 u 1 1 + u 9 ) d u = 2 5 2 0 1 Hence, A + B = 1 + 2 5 2 0 = 2 5 2 1 ∵ ∫ a b f ( x ) d x = ∫ a b f ( a + b − x ) d x ∵ sin 2 x + cos 2 x = 1 Let, u = sin x ⟹ d u = cos x d x
∫ sin 1 1 ( x ) cos 9 ( x ) d x ⇒ − 1 3 1 0 7 2 6 3 cos 2 ( x ) + 1 0 4 8 5 7 6 2 1 cos ( 4 x ) + 1 3 1 0 7 2 7 cos ( 6 x ) + 2 0 9 7 1 5 2 9 cos ( 1 2 x ) + 3 6 7 0 0 1 6 9 cos ( 1 4 x ) + 1 0 4 8 5 7 6 0 cos ( 2 0 x ) − 2 6 2 1 4 4 3 cos ( 8 x ) − 6 5 5 3 6 0 9 cos ( 1 0 x ) − 1 0 4 8 5 7 6 cos ( 1 6 x ) − 4 7 1 8 5 9 2 cos ( 1 8 x )
How to do the indefinite integral:
Apply this reduction formula five times:
∫ ( x cos m ) ( x sin n ) d x = − m + n ( x cos m + 1 ) ( x sin n − 1 ) + m + n n − 1 ∫ ( x cos m ) ( x sin n − 2 ) d x
giving:
− 2 0 1 ( x sin 1 0 ) ( x cos 1 0 ) − 3 6 1 ( x sin 8 ) ( x cos 1 0 ) − 7 2 1 ( x sin 6 ) ( x cos 1 0 ) − 1 6 8 1 ( x sin 4 ) ( x cos 1 0 ) − 5 0 4 1 ( x sin 2 ) ( x cos 1 0 ) + 2 5 2 1 ∫ ( x sin ) ( x cos 9 ) d x
Substitute u = cos ( x ) and d u = − s i n ( x ) d x : 2 5 2 1 ∫ u 9 d u ⇒ 1 0 u 1 0 .
All but the last summand of the indefinite integral evaluate to 0 at the integration limits as either the sine or the cosine is 0.
Therefore, evaluating the last term using the change of variable limits u - = − sin ( 0 ) = 0 and u + = − sin ( 2 π ) = − 1 :
− 2 5 2 1 × − 1 0 1 ⇒ 2 5 2 0 1
Problem Loading...
Note Loading...
Set Loading...
I = ∫ 0 2 π sin 1 1 x cos 9 x d x = ∫ 0 2 π sin 1 1 x cos 8 x ⋅ cos x d x = ∫ 0 2 π sin 1 1 x ( 1 − sin 2 x ) 4 ⋅ cos x d x = ∫ 0 1 u 1 1 ( 1 − u 2 ) 4 d u = ∫ 0 1 ( u 1 9 − 4 u 1 7 + 6 u 1 5 − 4 u 1 3 + u 1 1 ) d u = 2 0 1 − 1 8 4 + 1 6 6 − 1 4 4 + 1 2 1 = 2 5 2 0 1 Let u = sin x ⟹ d u = cos x d x
Therefore, A + B = 1 + 2 5 2 0 = 2 5 2 1 .